PRESCRIBING PATTERN OF DRUGS IN NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD): A CROSS-SECTIONAL STUDY FROM A TERTIARY CARE HOSPITAL IN KASHMIR - Fehmeeda Jalalie; Shagufta Parveen; Nisar A. Shah; Shah Immad (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Non-Alcoholic Fatty Liver Disease (NAFLD), now called as metabolic dysfunction-associated steatotic liver disease (MASLD), is a prevalent chronic liver condition that affects up to 25% of the global population. It encompasses a range of conditions, from simple non-alcoholic fatty liver (NAFL) to more severe stages such as non-alcoholic steatohepatitis (NASH), cirrhosis, and hepatocellular carcinoma.Objectives: This study aimed to evaluate the prescribing pattern of drugs in patients diagnosed with NAFLD, assessing the types of drugs prescribed, their classes, and the frequency of prescriptions in a tertiary care hospital setting.Methodology: A cross-sectional study was conducted over a period of three months at the Government Medical College (GMC) Srinagar, in collaboration with the Gastroenterology department. A total of 200 patients diagnosed with NAFLD were included for the study. Inclusion criteria included adult patients with NAFLD who consented to participate, while pregnant women, lactating women, patients with malignancy, and those unwilling to participate were excluded.Results: The findings revealed a predominant use of lipid-lowering agents and insulin sensitizers in NAFLD management. Lifestyle modifications, including dietary changes and physical activity, were commonly advised. The study also identified the common drugs prescribed, such as metformin, statins, and Vitamin E, reflecting the medical approach towards managing the disease and its co-morbidities. The prescribing patterns were influenced by factors like age, gender, and the presence of additional health conditions.Conclusion: This study highlighted the current trends in pharmacological interventions for NAFLD, demonstrating the heavy reliance on lifestyle changes and specific drug classes. The results suggest a growing understanding of the role of medication in managing NAFLD, alongside lifestyle modifications, to prevent disease progression.